Neural correlates of visualizations of concrete and abstract words in preschool children: a developmental embodied approach - D’Angiulli, Amedeo; Griffiths, Gordon; Marmolejo-Ramos, Fernando (Frontiers in Psychology, 2015)
The neural correlates of visualization underlying word comprehension were examined in preschool children. On each trial, a concrete or abstract word was delivered binaurally (part 1: post-auditory visualization), followed by a four-picture array (a target plus three distractors) (part 2: matching visualization). Children were to select the picture matching the word they heard in part 1. Event-Related Potentials (ERPs) locked to each stimulus presentation and task interval were averaged over sets of trials of increasing word abstractness. ERP time-course during both parts of the task showed that early activity (i.e. < 300 ms) was predominant in response to concrete words, while activity in response to abstract words became evident only at intermediate (i.e. 300-699 ms) and late (i.e. 700-1000 ms) ERP intervals. Specifically, ERP topography showed that while early activity during post-auditory visualization was linked to left temporo-parietal areas for concrete words, early activity during matching visualization occurred mostly in occipito-parietal areas for concrete words, but more anteriorly in centro-parietal areas for abstract words. In intermediate ERPs, post-auditory visualization coincided with parieto-occipital and parieto-frontal activity in response to both concrete and abstract words, while in matching visualization a parieto-central activity was common to both types of words. In the late ERPs for both types of words, the post-auditory visualization involved right-hemispheric activity following a “post-anterior” pathway sequence: occipital, parietal and temporal areas; conversely, matching visualization involved left-hemispheric activity following an “ant-posterior” pathway sequence: frontal, temporal, parietal and occipital areas. These results suggest that, similarly for concrete and abstract words, meaning in young children depends on variably complex visualization processes integrating visuo-auditory experiences and supramodal embodying representations.